Youth Phenomenon: An Overview of Stress Levels among Adolescents with Body Shaming Experience - Sang Ayu. Eka Putri Wahyuni; Ni Made Dian Sulistiowati; Putu Ayu Emmy Savitri Karin; I Ketut Dian Lanang Triana; I Gusti Agung Ayu Adinda Wulandari (Caring: Indonesian Journal of Nursing Science, 2024)
Adolescence is characterized as a transitional phase between childhood and adulthood. Therefore, individuals undergo numerous adaptations necessary to successfully navigate developmental tasks associated with adolescence. Adolescents experience various physical, emotional, and social changes, which, if misaligned with their expectations, can lead to psychological challenges, particularly stress. This study investigates the stress levels among adolescents who have experienced body shaming at SMP N 2 Dawan. This study was a quantitative study with a cross-sectional method conducted among adolescents who experienced body shaming. The study sample consisted of 101 participants selected through purposive sampling based on predetermined inclusion and exclusion criteria. Data were collected using the Adolescent Stress Questionnaire-27 (ASQ-27) and analyzed using a computerized program. The results revealed that a significant proportion of respondents (69.3%) experienced moderate levels of stress. The primary sources of stress were identified in the domains of teacher interactions and home life. These findings highlight the need for effective stress alleviation strategies to promote improved mental health outcomes among adolescents.